Zakonske in postopkovne ovire na področju varstva narave pri intenziviranju gospodarjenja z gozdom - Čibej, Ljubo (Gozdarski vestnik, 2011)
The article presents legal and procedural obstacles in the field of nature protection that concessionaires in state-owned forests meet while performing forest management plans and planning and constructing forest traffic roads.
Keywords: environmental protection; varstvo narave; Natura 2000; gozdne prometnice; zakonodaja; državni gozdovi; koncesija; Slovenia; Slovenija